LIBERALISME DAN FUNDAMENTALISME ISLAM DI KALANGAN DOSEN DAN MAHASISWA (STUDI KASUS DI FAKULTAS USHULUDDIN DAN STUDI ISLAM UIN SUMATRA UTARA MEDAN) - Mulia, Sukma; Fadillah, Heny; Adenan, Adenan; Arrasid, Saif (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study analyzes Islamic liberalism and fundamentalism among students and lecturers of the Faculty of Ushuluddin and Islamic Studies, State Islamic University of North Sumatra, Medan. The main focus of this study is to understand the diversity of religious views, the factors that influence them, and the dynamics that emerge in the classroom and academic forums, and their impact on the academic environment. Using a qualitative approach, this study identifies ideological tendencies (liberal, moderate, fundamental) among respondents, as well as the characteristics of religious expression from each group. Factors such as educational and social background, the influence of student organizations and Islamic forums, and religious literacy and reading are analyzed to explain the formation of these views. This study also examines the situation of interaction between groups in the academic environment, the role of the faculty in responding to differences of opinion. The results of this study are expected to provide a comprehensive picture of the positive and negative impacts of this plurality of religious views and emphasize the urgency of moderation to create an inclusive and harmonious academic environment at the Faculty of Ushuluddin and Islamic Studies, State Islamic University of North Sumatra, Medan.